Rural-urban dynamics [ livelihoods, mobility and markets in African and Asian frontiers - Agergaard, Jytte , 1960-; Fold, Niels; Gough, Katherine V. , 1963- (Routledge studies in human geography, 2010)
This book adopts a fresh approach to the issue of rural-urban dynamics through a study of the changing nature of livelihoods, mobility and markets in ten study sites across four countries of Africa and Asia.